2001
DOI: 10.1007/bf02234704
|View full text |Cite
|
Sign up to set email alerts
|

Early and late (ten years) experience with circular stapler hemorrhoidectomy

Abstract: Mechanical hemorrhoidectomy is a promising new option in the treatment of all patients eligible for a surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 16 publications
2
47
0
3
Order By: Relevance
“…O'Donovan et al 12 (1994) and Pernice et al 13 (2001) demonstrated that ketorolac is also effective in controlling postoperative pain and reducing urinary retention following hemorrhoidectomy. According to Carney et al (2001) 5 ketorolac reduced the use of opioids and lowered the morbidity during the first 48 hours after pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…O'Donovan et al 12 (1994) and Pernice et al 13 (2001) demonstrated that ketorolac is also effective in controlling postoperative pain and reducing urinary retention following hemorrhoidectomy. According to Carney et al (2001) 5 ketorolac reduced the use of opioids and lowered the morbidity during the first 48 hours after pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Visual analogue scoring initiated at 12 hours post-operatively following the weaned out effect of spinal anaesthesia. Scores at 24 hours, day 3, day 7, day 15 was significantly low in group B as against group A (Table 10, 11,12,13). The…”
mentioning
confidence: 86%
“…12 It has also made the surgery for haemorrhoids more patient friendly. 13 In the present study patients were divided into two groups A and B i.e. those undergoing Milligan Morgan haemorrhoidectomy and stapled haemorrhoidectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stapled mucosectomy is definitely a less painful procedure, but it does not lead to a significant earlier return to work and is fraught with risks of fatal complications and development of new symptoms like persistent pain and fecal urgency in long term. 6,7 We innovated a procedure combining radiofrequency ablation followed by a circumferential plication of the prolapsing mucosa [8][9] and found it to be a quicker, convenient, less painful and an equally effective procedure for patients with rectal mucosal prolapse. This paper describes the technique of radiofrequency ablation and plication and presents the results of a randomized controlled trial that compared our technique with conventional ligature and excision procedure in patients with rectal mucosal prolapse.…”
Section: Introductionmentioning
confidence: 99%